Maintaining everyday life praxis in the time of COVID-19 pandemic measures (ELP-COVID-19 survey). (3rd September 2020) - Pišot, Saša; Milovanović, Ivana; Šimunič, Boštjan; Gentile, Ambra; Bosnar, Ksenija; Prot, Franjo; Bianco, Antonino; Lo Coco, Gianluca; Bartoluci, Sunčica; Katović, Darko; Bakalár, Peter; Kovalik Slančová, Terézia; et al.
Abstract: Background: The extreme social circumstances caused by declared COVID-19 pandemic deeply intervene people's everyday life and should not be neglected but seen through the view of social reality pinpointing the 'ordinary' people. In this article, authors explored basic segments of everyday and their subjective perception to what extent sleeping habits, physical inactivity, physical activity, nutritional habits and smoking have changed. Methods: The online survey was conducted in nine European countries (Bosnia and Herzegovina, Croatia, Greece, Kosovo*, Italy, Serbia, Slovakia, Slovenia and Spain) in 4108 participants, aged 15–82 years. The survey took place 30–40 days after World Health Organization declared COVID-19 pandemic state, from 15 April to 3 May 2020. Results: The results have shown 30 min longer sleeping time, 50% longer physical inactivity time, 65% longer screen time, 43% shorter walking time, 24% shorter sport time and 37% longer physical work time. Additionally, body mass gains (0.3 kg) could be explained in 20.6% with meals sizes, unhealthy food consumption, screen time and sport time. Further, respondents reported more regular meals (44%) and healthier meals with less alcohol consumption and less smoking, which have been positive outcomes of home confinement. Conclusion: The findings draw attention to negative changes in everyday praxis (inactivity, body mass gain) after such a short period. Because of possible risk to population's health (especially of countries such as Italy and Spain with serious threat and more stringent measures), findings enable development of recommendations for maintaining healthy lifestyle habits with minimal negative health consequences in similar pandemic circumstances.